Emotions, technology, and health - Tettegah, Sharon Y.; Garcia, Yolanda Evie (Emotions and technology., 2016)
"Emotions, technology, and health examines how healthcare consumers interact with health technology, how it mediates interpersonal interactions, and the effectiveness of technology in gathering health-related information in various situations. The book discusses the use of technology to monitor patients' emotional responses to and treatment of mental and physical illness. It describes the use of technology in managing emotions within and between individuals, and addresses the implications for the design and use of devices that gather behavioral health data and contribute to healthcare interventions. The volume also assesses different situations in which technology is a key component of the health intervention--such as tablet use in educating elementary school students with social skills difficulty, physical activity monitoring for children at risk for obesity, and teleconferencing for older adults at risk of social isolation." -- Provided by publisher